Food Security Now: New Norm or False Dawn? - Teng, Paul P.S. (2016)
The world is experiencing a situation of slower economic growth and lower commodity prices translated into relatively lower Food Price Indices for many countries. This “new norm” benefits urban consumers but poses potential problems for agribusiness and rural producers, since, inter alia, it discourages them to invest. Will this “new norm” last? Or will it prove a “false dawn”?